2021
DOI: 10.2196/23097
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Public Adoption of COVID-19 Prevention and Treatment Information During an Infodemic: Cross-sectional Survey Study

Abstract: Background With the spread of COVID-19, an infodemic is also emerging. In public health emergencies, the use of information to enable disease prevention and treatment is incredibly important. Although both the information adoption model (IAM) and health belief model (HBM) have their own merits, they only focus on information or public influence factors, respectively, to explain the public’s intention to adopt online prevention and treatment information. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…This finding is similar to a multi-country study and a mixed approach study from Eastern Ethiopia that reported the same trends [12,16]. In addition, studies revealed that the individual's adoption of the precautionary measures depends on the individual's belief towards the government directions, protectiveness, and effectiveness of Covid-19 preventive measures [12,20,21,29,30]. Besides this, those who had access to water supply were 2.92 times more likely to practice preventive measures compared to those who do not have.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is similar to a multi-country study and a mixed approach study from Eastern Ethiopia that reported the same trends [12,16]. In addition, studies revealed that the individual's adoption of the precautionary measures depends on the individual's belief towards the government directions, protectiveness, and effectiveness of Covid-19 preventive measures [12,20,21,29,30]. Besides this, those who had access to water supply were 2.92 times more likely to practice preventive measures compared to those who do not have.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the continuance usage intention of consumers can grow accordingly. This result is in line with previous references [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. The necessity of electronic word of mouth was stressed, and it is suggested that e-payment providers should maintain consumers' confidence of use by providing consumers with secure and quality technologies of perceived usefulness to lay the foundation of establishing electronic word of mouth and improving continuance usage intention.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 87%
“…Studies on eWOM mainly focus on exploring the multi-faceted nature of sales and consumer behavior, including consumers' information adoption and providing evidence for effects on product preferences and effects on continuance usage intention [69][70][71][72][73][74]. In addition, e-commerce in the business model has become the norm [75] and eWOM has a broad effect on consumer attitudes and behaviors, including consumers' continuance usage intention [76][77][78].…”
Section: Electronic Word Of Mouth and Continuance Usage Intentionmentioning
confidence: 99%
“…Based on IAM, users make judgments about the usefulness of information in conjunction with their personal beliefs, which further influence their information adoption behavior [30,33]. According to previous studies, users will recognize information when it is consistent with their personal beliefs, meaning that they find the information to be useful to themselves [34]. In online communities, this recognition may influence some of the users' behaviors, such as following someone who provides the information that they need, or liking and reposting a post that they agreed with.…”
Section: Hypothesis 221 Perceived Usefulnessmentioning
confidence: 99%